The Andean Community and Ecuador’s Foreign Policy between 2007-2017: A Constructivist Approach that Evidences the Fragile Collective Identity of the CAN - Osorno Holguín, Sofía (2025)
This article analyzes Ecuador’s foreign policy during Rafael Correa’s administration as a determining factor in changing Ecuador’s identity within the international system. It argues that this new identity created frictions with the Andean Community (CAN) and several of its members, such as Colombia and Peru, further weakening the already fragile collective identity. The analysis is framed within constructivism, specifically drawing from national role theory. To determine the specific role Ecuador played in the international system and how it interacted with the CAN during Rafael Correa’s government, two fundamental instruments that shaped foreign policy are considered: the 2007–2010 National Development Plan and the 2009–2013 National Plan for Good Living. As a result, the study concludes that there was indeed a shift in Ecuador’s ideas, interests, and identity. The new concept of national sovereignty, combined with the interest in reconfiguring the international order and distancing from “hegemonic” actors such as the United States and the European Union, are key elements that justify Ecuador’s break with the CAN. These elements were reflected in Ecuador’s new role within the international community.